Nanoalloying effects on the catalytic activity of the formate oxidation reaction over AgPd and AgCuPd aerogels. Issue 27 (3rd May 2019) - Wang, Qiao; Chen, Fuyi; Guo, Longfei; Jin, Tao; Liu, Huazhen; Wang, Xiaolu; Gong, Xiaofang; Liu, Yaxing
Abstract : Nanoalloying effects and dealloying endow D-AgCuPd aerogels with significantly enhanced FOR activity compared to their monometallic, bimetallic and trimetallic counterparts. Abstract : Direct formate fuel cells (DFFCs) are promising energy conversion devices due to their high power density, easy fuel storage/transport and good environmental compatibility, but even platinum-group-metal (PGM, e.g. Pt and Pd) electrocatalysts are still limited by their low catalytic activity and stability for formate oxidation reactions (FORs) in alkaline media. Herein, the promotional roles of Ag and Cu elements in AgPd and AgCuPd nanoalloys and the dealloying treatment of AgCuPd nanoalloys towards FOR catalysis are studied. Various Ag x Pd100− x, Ag y Cu50− y Pd50 and dealloyed Ag y Cu50− y Pd50 aerogels (denoted as D-Ag y Cu50− y Pd50 hereafter) are synthesized, and their electrochemical performances are compared with those of state-of-the-art Pd/C catalysts. The D-Ag25 Cu25 Pd50 nanoalloy exhibits significantly enhanced FOR activity with a mass activity of 2.73 A mg −1 and a specific activity of 10.10 mA cm −2 and a higher current density in the chronoamperometry test than that of commercial Pd/C and most previously reported Pd-based catalysts. A downshift of the d-band centre is observed in D-Ag25 Cu25 Pd50 aerogels compared to the pure Pd catalyst. This work highlights the dual-enhancement mechanism of the nanoalloying effect: (1) alloying the Pd surface with Ag atoms causes an electronic effect, which essentially weakens the binding between Pd and the absorbed hydrogen, and (2) alloying the Pd surface with Cu atoms causes an oxophilic effect, which assists the formation of OH species to improve the oxidative removal of the absorbed hydrogen.